2011
DOI: 10.1111/j.1365-2842.2011.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between masticatory performance using a colour-changeable chewing gum and jaw movement

Abstract: The purpose of this study was to investigate the relationship between masticatory performance as determined using a colour-changeable chewing gum and mandibular movements. Subjects comprised 45 fully dentate adults (23 men, 22 women; mean age, 28·1 years). The gum was chewed for a specified number of chewing strokes (20, 40, 60, 80, 120 or 160 strokes) without any instructions as to chewing side. A colourimeter was used to measure L*, a* and b* values (CIE-L*a*b* colour system) for the chewed gum, then the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 36 publications
6
94
0
3
Order By: Relevance
“…Corroborating these results, previous studies have shown positive correlation between mandibular movement velocity and chewing performance (15,16) . This fact suggests that higher velocity during the closing phase of the masticatory cycle transmits a greater amount of energy to the food bolus, consequently allowing more efficient crushing.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Corroborating these results, previous studies have shown positive correlation between mandibular movement velocity and chewing performance (15,16) . This fact suggests that higher velocity during the closing phase of the masticatory cycle transmits a greater amount of energy to the food bolus, consequently allowing more efficient crushing.…”
Section: Discussionsupporting
confidence: 78%
“…Mandibular movement variables have been associated with masticatory performance. Better masticatory performance has been related to greater vertical mandibular range of motion, higher closing velocity, and shorter duration of the masticatory cycle closing phase (15,16) . The study of the behavior of the kinematic variables of deliberate unilateral and habitual mastication in healthy individuals can contribute to the understanding of the possible impact of the pattern adopted on masticatory performance in cases of disorders that interfere with the chewing function, such as TMD, oral breathing, and occlusal alterations.…”
Section: Introductionmentioning
confidence: 99%
“…With the progression of chewing, the color of the chewing gum turns from yellowish-green to red because the yellow and blue dyes seep into saliva, and the red dye appears as a result of elution of the citric acid [12,14]. The gum initially had a greenish color and became more-and-more reddish with the duration and intensity of chewing, and there is a strong correlation between color change and masticatory performance and ability.…”
Section: -Id As Well As Four Ohip Questions Concerning Masticatorymentioning
confidence: 99%
“…This method is easy, simple, and quick, with no need for bulky equipment, and it has advantages in stimulating a natural and stable act of chewing while still allowing complete recovery of the test item. Color-changeable chewing gum has been applied in various fields [12].…”
Section: Research Articlementioning
confidence: 99%
“…Este método envolve a determinação da performance mastigatória pela avaliação da alteração de cor da goma de mascar após o teste (Komagamine et al, 2011;Komagamine et al, 2012;Hama et al, 2014aHama et al, , 2014b. O método é considerado simples, efetivo, rápido, além de apresentar correlação positiva com o método que utiliza as peneiras granulométricas (Hama et al, 2014a).…”
Section: Função Mastigatóriaunclassified